Calculation of Thermal Stress in Elastohydrodynamic Lubrication of Line Contact. (November 2020) - Lu, Zunyou; Lu, Yanjun
Abstract: A numerical method is proposed to calculate the surface thermal stresses of solids in thermal elastohydrodynamic lubrication of line contact. According to the method, the material line thermal expansion coefficients of lubricated contact surface are calculated after obtaining the pressure and temperature that meet the convergence conditions, then the thermal stresses are calculated. The results show that the values of the circumferential thermal stress and the axial thermal stress are negative. Both the circumferential thermal stress and the axial thermal stress are compressive stresses. When the entrainment speed Increases, the absolute values of the circumferential and axial thermal stresses become larger.